Analysis of the power conversion efficiency of perovskite solar cells with different materials as Hole-Transport Layer by numerical simulations - Casas, Guillermo (2017)
In this paper, a theoretical study of different p-p-n perovskite solar cells has been performed by means of computer simulation. Effects of the offset level upon the power conversion efficiency (PCE) of these devices have been researched using five different materials such as spiro-OMeTAD, Cu₂O, CuSCN, NiO and CuI, as Hole Transporting Layer (HTL). The Solar Cells Capacitance Simulator (SCAPS)-1D has been the tool used for numerical simulation of these devices. A strong dependence of PCE has been found with the difference between the Maximum of the Valence Band of the HTL and perovskite materials, and with the doping level in p-type perovskite layer. A minimum value of hole mobility in the HTL has been also found, below which the PCE is reduced. Efficiencies in the order of 28% have been obtained for the Cu₂O/Perovskite/TiO₂ solar cell. Results obtained in this work show the potentiality of this promising technology.